Validating a Novel Emotional Intelligence Instrument for Resident Physicians. Issue 3 (September 2022) - McCallum, R. Steve; Kirkpatrick, Baileigh A.; Heidel, Robert E.; Rocconi, Louis; Price, Chelsea N.; Gee, Kaylan N.; Lewis, James M.
To construct and validate a scale of emotional intelligence (EI) for the medical field, n = 80 resident physicians responded to a 69-item self-report measure during the pilot phase of development of the Scale of Emotional Functioning: Medicine (SEF:MED). Based on multiple-phase item and structural analyses, a final 36-item version was created based on data from n = 321 respondent residents. Initially exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) supported the expected three-factor solution as did additional CFA from a second sample of n = 113 participants. Internal consistency reliabilities obtained from the original n = 321 residents for the three SEF:MED subscales of Interpersonal Skills (IS), Emotional Awareness (EA), and Emotional Management (EM) were 0.81, 0.82, and 0.84, respectively. Alphas for the second CFA data set were 0.89, 0.87, and 0.88 for IS, EM, and EA, respectively. In addition, the SEF:MED was validated by comparing it to related measures (i.e., the Profile of Emotional Competence (PEC) and the Maslach Burnout Inventory-Human Services Survey for Medical Personnel [MBI-HSS (MP)]); Correlation coefficients between the Total EI composite on the SEF:MED and the PEC global scales ranged from r = 0.64 to 0.68. Finally, correlation coefficients from the Total EI composite on the SEF:MED significantly related to the MBI-HSS (MP) Emotional Exhaustion (EE), Depersonalization (DP), and Personal Accomplishment (PA) scales (r = −0.50, −0.44, and 0.52, respectively). The SEF:MED may provide useful data to physicians and other medical professionals as they consider their own well-being and how it may affect care of their patients.